2014
DOI: 10.1371/journal.pone.0097091
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Complex Intervention to Support Personal Recovery: A Qualitative Study Nested within a Cluster Randomised Controlled Trial

Abstract: ObjectiveTo investigate staff and trainer perspectives on the barriers and facilitators to implementing a complex intervention to help staff support the recovery of service users with a primary diagnosis of psychosis in community mental health teams.DesignProcess evaluation nested within a cluster randomised controlled trial (RCT).Participants28 interviews with mental health care staff, 3 interviews with trainers, 4 focus groups with intervention teams and 28 written trainer reports.Setting14 community-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 19 publications
(20 reference statements)
2
48
0
Order By: Relevance
“…The findings further suggest implementation issues surrounding the way in which the intervention was implemented which included a lack of change in the relationships between staff and service users, and/or formulaic and non-individualised use of the recovery tools. These findings are consistent with the staff process evaluation, which specifically focused on the implementation of the intervention and highlighted barriers to implementation within routine practice, including organisational readiness and fit with routine targets and outcomes [29].…”
Section: 'If You've Lost Hope Then You've Lost Life (
) So It's Good supporting
confidence: 83%
See 1 more Smart Citation
“…The findings further suggest implementation issues surrounding the way in which the intervention was implemented which included a lack of change in the relationships between staff and service users, and/or formulaic and non-individualised use of the recovery tools. These findings are consistent with the staff process evaluation, which specifically focused on the implementation of the intervention and highlighted barriers to implementation within routine practice, including organisational readiness and fit with routine targets and outcomes [29].…”
Section: 'If You've Lost Hope Then You've Lost Life (
) So It's Good supporting
confidence: 83%
“…However rigid and formulaic implementation was not found to be helpful. Previous research has indicated that staff tend to focus on particular tasks as evidence of 'doing' recovery thus, "omitting the underlying philosophy of recovery-orientated practice" [29,30].…”
Section: Implications For Practicementioning
confidence: 99%
“…The REFOCUS intervention for community mental health teams (case study 3) took place at a similar time and Leamy et al . () state on p4 ‘the organizational changes were of such intensity that workers reported focusing on and prioritizing their own survival’. It may be overly ambitious to try to engage members of staff with a training/change programme at all in such overwhelmingly negative circumstances.…”
Section: Resultsmentioning
confidence: 99%
“…; Hungerford ; Leamy et al . ). The challenge for mental health nurses is to develop sustainable and productive relationships with MHW that enhance workforce capability, are responsive to client and family needs, and embrace the recovery paradigm.…”
Section: Discussionmentioning
confidence: 97%